Pelatihan Kewirausahaan Pembuatan Produk Ecoprint Mengunakan Teknik Pounding Dengan Bahan Daun Eksotik Dari Sekitar Tempat Tinggal Untuk Mendorong Perekonomian Masyarakat - Kurniawan, Yohanes Jhony; Julianto, Heppy; Suhartono, Suhartono (CV. Ulil Albab Corp, 2025)
This PKM (Community Service) activity aims to increase the desires of students, alumni, STMA Trisakti leaders, accompanying lecturers, and the community around the STMA Trisakti campus, and to carry out Entrepreneurship training activities for Making Ecoprint Products Using Pounding Techniques with Exotic Leaf Material from Around the Residence. With the Entrepreneurship Training method for Making Ecoprint Products. There were 18 participants who attended this PKM. The results of this PKM were 18 ecoprint products using the pounding technique with exotic leaf materials from around the residence.